Naturally acquired immunity to Plasmodium falciparum. - Day, K; Marsh, K (1991)
Malaria infections induce multiple humoral and cellular responses, most of which are probably not protective. This discussion of the epidemiology of acquired immunity to malaria will concentrate on two main areas: first, the relationship between parasitism and disease in endemic settings and the constraints placed on determining which responses are important in acquired protective immunity; second, the central importance of antigenic diversity in the host-parasite relationship. The emphasis throughout, unless otherwise stated, will be on the major human pathogen Plasmodium falciparum.